Indigenous Techniques and Practices for Management of Bio-resources: a Naga Experience - Martemjen; lkr, Lanusashi; Tiakumla (International Journal of Bio-resource and Stress Management, 2023)
Indigenous Peoples with centuries of their intimate links and relationship with nature has broad knowledge base on the complex ecological system. Their Knowledge, techniques and practices have come through prolonged series of observation and experiences transmitted from generation to generation. They have a clear perception on the bio-resource for generating ecological services and on which their entire life depend, that they have effectively developed a stake in managing and conserving the bio-resources in their surroundings. Nagaland with its total geographical area of 16,579 km2 is situated in the rich Indo-Burman Biodiversity belt. For centuries, Nagas have been directly or indirectly dependant on the natural environment for sustenance. Even today they are known for their intimate link with environment that forms an inalienable part of their life. The proposed paper attempts to understand the techniques and practices used by the Nagas in the management of bio-resources as cause and effect functional relationships. It further delivers into the crucial role of the Indigenous Knowledge that form seamless part of their heritage thereby effectively managing and conserving the bio-resources of the state.